Use of artificial intelligence in ophthalmology: a narrative review - Martins, Thiago Gonçalves dos Santos; Schor, Paulo; Mendes, Luís Guilherme Arneiro; Fowler, Susan; Silva, Rufino (São Paulo Medical Journal, 2022)
BACKGROUND: Artificial intelligence (AI) deals with development of algorithms that seek to perceive one’s environment and perform actions that maximize one’s chance of successfully reaching one’s predetermined goals. OBJECTIVE: To provide an overview of the basic principles of AI and its main studies in the fields of glaucoma, retinopathy of prematurity, age-related macular degeneration and diabetic retinopathy. From this perspective, the limitations and potential challenges that have accompanied the implementation and development of this new technology within ophthalmology are presented. DESIGN AND SETTING: Narrative review developed by a research group at the Universidade Federal de São Paulo (UNIFESP), São Paulo (SP), Brazil. METHODS: We searched the literature on the main applications of AI within ophthalmology, using the keywords “artificial intelligence”, “diabetic retinopathy”, “macular degeneration age-related”, “glaucoma” and “retinopathy of prematurity,” covering the period from January 1, 2007, to May 3, 2021. We used the MED-LINE database (via PubMed) and the LILACS database (via Virtual Health Library) to identify relevant articles. RESULTS: We retrieved 457 references, of which 47 were considered eligible for intensive review and critical analysis. CONCLUSION: Use of technology, as embodied in AI algorithms, is a way of providing an increasingly accurate service and enhancing scientific research. This forms a source of complement and innovation in relation to the daily skills of ophthalmologists. Thus, AI adds technology to human expertise.